Diagnosis and management of chronic wound in dog- A case report - D. Kakki (The Indian Veterinary Journal, 2024)
A 4 months old desi dog was presented to Veterinary clinic with a history of non-healing wound in the neck. On clinical examination it was found that there was a foreign body causing chronic wound, which was successfully removed under general anaesthesia and patient had uneventful recovery by a combination therapy of anti-inflammatory and antibiotics .